Homework assignment and student achievement in OECD countries - Torberg Falch; Marte Rønning (Statistics Norway, Research Department, 2012)
This paper analyzes the effect of assigning homework on student achievement using data from 16 OECD countries that participated in TIMSS 2007. The model exploits withinstudent variation in homework across subjects in a sample of primary school students who have the same teacher in two related subjects; mathematics and science. Unobserved teacher and student characteristics are thus conditioned out of the model and the identification rests on random relative homework assignment across the subjects at the teacher and classroom level. We find a modest, but statistically significant effect of homework. The effect varies across countries, and it is positively correlated with the amount of time students and teachers spend in the classroom.
Keywords: I20; I21; I24; I; 330; Homework assignment; student achievement